Novel and Efficient Procedure for the Preparation of Two Pyridine Dicarboxylic Acid Derivatives - G. U. Guoliang; L. U. Ming (E-Journal of Chemistry)
New strategies for the synthesis of two pyridine dicarboxylic acid derivatives namely; 4-(2-(2,6-dicarboxypyridin-4-yl)vinyl)pyridine-2,6-dicarboxylic acid and 2,6-bis(2-(2,6–dicarboxy-pyridin-4-yl)vinyl)pyridine have been described. New oxidant used is a good example of green chemistry technology and the synthesis procedure harvest a high-purity product at a high yield.